The Influence Of Leadership Style And Work Motivation On Employee Performance At PT Rayandra Ataullah Aryaguna, South Tangerang - Herni, Yulies; Pratama, Angga; Karlina, Dira (Jurnal Price : Ekonomi dan Akuntasi, 2024)
The purpose of this study was to determine the effect of leadership style and work motivation on employee performance at PT. Rayandra Orullah Aryaguna. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of respondents. Data analysis involved validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of this study show that leadership style has a significant effect on employee performance, with a determination coefficient indicating a substantial relationship. Hypothesis testing confirmed the significance of this effect. Work motivation also has a significant impact on employee performance, supported by the coefficient of determination and hypothesis testing results. Leadership style and work motivation, when considered together, have a significant effect on employee performance, as indicated by the regression equation. The coefficient of determination suggests that a significant portion of the variance in employee performance can be explained by these factors, while the remaining variance is influenced by other factors. Hypothesis testing also confirms the significance of the combined effect.